Analisis Penyebab Kecelakaan Kerja Dengan Metode Human Factor Analysis and Classification System di Industri Batu Bara, Virginia Barat - Abdurrahman Faiz Musyaffa; Muhammad Alvin Faiz A; Ajeng Ar Rayhaani Cindy; Bungka Rico Hutabalian; Budi Sulistiyo Nugroho (LPPM Institut Teknologi Petroleum Balongan, 2024)
A On January 9 2014, a workplace accident in the West Virginia coal industry saw the chemical 4- Methylcyclohexane Methanol (MCHM) leak from a storage tank into the Elk River, contaminating drinking water sources for residents in 9 counties. This study used the Human Factors Analysis and Classification System (HFACS) method to analyze the causes of the accident and provide improvement recommendations. The percentage analysis showed that the main cause 27% was weaknesses in organizational procedures, such as lack of safety guidelines, risk management and equipment maintenance. This had a domino effect on other factors, including inadequate supervision and unsafe acts by workers. To prevent similar accidents, the company needs to improve the organizational system by focusing on developing a structured inspection system, enforcing SOPs, risk management and safety evaluation. In addition, internal communication should be improved, regulations should be adhered to, and safety culture should be a top priority. This implementation is expected to prevent the recurrence of similar accidents in the future, protecting workers, the environment and the surrounding community.